Association Between Smell Loss, Disease Burden, and Dupilumab Efficacy in Chronic Rhinosinusitis with Nasal Polyps - Soler, Zachary M.; Patel, Zara M.; Mullol, Joaquim; Mattos, Jose; Nash, Scott; Xia, Changming; Wang, Zhixiao; Borsos, Kinga; Corbett, Mark; Jacob-Nara, Juby A.; Sacks, Harry; Rowe, Paul; et al. (American journal of rhinology & allergy, 2025)
Objective To evaluate the association between smell loss and other aspects of disease, and evaluate dupilumab efficacy in patients with severe chronic rhinosinusitis with nasal polyps (CRSwNP) and moderate or severe smell loss. Methods This post-hoc analysis of the SINUS-24/52 studies (NCT02912468/NCT02898454) analyzed nasal polyp score (NPS, 0−8), nasal congestion/obstruction (NC, 0−3), Lund-Mackay CT-scan score (LMK-CT, 0−24), rhinosinusitis severity visual analog scale (RS-VAS, 0-10), and 22-item Sinonasal Outcome Test (SNOT-22, 0−110) according to baseline monthly average patient-reported loss of smell scores (LoS, 0−3) of >1 to 2 (moderate) or >2 to 3 (severe) in patients randomized to dupilumab 300 mg or placebo every 2 weeks. Results Of 724 patients randomized, baseline LoS was severe in 601 (83%) and moderate in 106 (15%). At baseline, severe versus moderate LoS was associated with 1-point greater severity of NC (odds ratio [OR] 6.01 [95% confidence interval, (CI) 3.95, 9.15]), 5-point greater severity of LMK-CT (OR 2.19 [1.69, 2.85]), and 8.9-point greater severity of SNOT-22 (OR 1.35 [1.20, 1.49]). At Week 24, least squares mean differences (95% CI) dupilumab versus placebo in change from baseline were: NPS −1.90 (−2.56, −1.25) and −1.95 (−2.20, −1.70) in the moderate and severe baseline LoS subgroups, respectively; NC −.35 (−.64, −.06) and −1.00 (−1.13, −.87); LMK-CT −6.30 (−7.88, −4.72) and −6.22 (−6.82, −5.63); RS-VAS −1.18 (−2.20, −.16) and −3.47 (−3.90, −3.03); and SNOT-22 −7.52 (−14.55, −.48) and −21.72 (−24.63, −18.82); all nominal P < .05 versus placebo. Improvements with dupilumab in NC, RS-VAS, and SNOT-22 were statistically greater in patients with severe versus moderate baseline LoS. Conclusion Significant smell impairment in severe CRSwNP is associated with significant disease (NC, RS-VAS, LMK), health-related quality of life impairment (SNOT-22), asthma, and non-steroidal anti-inflammatory drug-exacerbated respiratory disease. Dupilumab significantly improved NPS, NC, LMK-CT, RS-VAS, and SNOT-22 in subjects with moderate and severe baseline smell loss.